Respuestas

2012-04-08T21:16:55+02:00

2x = 5 + x        x=5

7 = 4x - 1         7+1=4x            8/4=x        x=2

x = 2x - 3         x - 2x = -3      -x = -3  se simplifican los signos x=3

3x =10 - x        3x - x= 10        2x=10      x= 10/2         x=5

3 = 2x - 5         3 + 5=2x          8/2=x        X=2

x = 5x - 8         8=5x - x          8=4x          X=2

x = 6 - x           2x=6              x=3

 

5 = 2x + 3         5-3=2x         2/2=x

x = 3x - 12        12=3x+x      12/4=x     x=3

5x = 2 + x        5x-x=2        x=2/4     x=1/2

2 = 4x - 1       2+1=4x         3/4=x

x = 4x - 1       1=4x-x         x=1/3

2012-04-08T21:28:28+02:00

a)      2x= 5+x

2x-x=5

x=5

b)      7=4x-1

7+1=4x

8=4x

8/4=x

x=2

c)       x=2x-3

3=2x-x

3=x

x=3

d)      3x=10-x

3x+x=10

4x=10

x=10/4

e)      3=2x-5

3+5=2x

8=2x

8/2=x

x=8/2

f)       x=5x-8

8=5x-x

8=4x

x=8/4

x=2

g)      x=6-x

x+x=6

2x=6

x=6/2

x=3

h)      5=2x+3

5-3=2x

2=2x

x=2/2

x=1

i)        x=3x-12

12=3x-x

12=2x

12/2=x

x=6

j)        5x=2+x

5x-x=2

4x=2

4/2=x

x=2

k)      2=4x-1

2+1=4x

3=4x

x=3/4

 

l)        x=4x-1

1=4x-x

1=3x

x=1/3